Digitalization of Social Movements in the Metaverse Era: A Study on Mining Resistance in Salipolo, Pinrang Regency, Indonesia - Kurnia Sulistiani; Muhammad Al Hamid; Gustiana Kambo (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The social movement in Salipolo Village, Pinrang Regency, Indonesia, opposing the development of sand mining, reflects a response to development policies perceived as environmentally destructive and threatening to the livelihoods of the local community. This study aims to explore how digitalization influences the dynamics of this social movement, focusing on the use of social media and data-based technologies as advocacy tools. The research findings show that digital transformation has opened new avenues for the Salipolo community to organize, document environmental impacts, and expand the reach of their movement more broadly. The use of visual data, such as maps of affected areas and environmental impact simulations, has strengthened their position in negotiations with the government and mining companies. This collaboration not only provides moral and material support but also introduces more effective advocacy strategies, broadening the impact of the social movement. The study demonstrates that digitalization has empowered the Salipolo community to fight for justice and policy changes that align more closely with their interests. Therefore, this social movement is not limited to mass actions but also involves the use of technology to strengthen the community’s bargaining power in the face of detrimental development policies. Keywords: Social Movement, Digitalization, Mining Rejection, Cross-Community Collaboration, Digital Advocacy.